Synthesis and characterization of a novel eight-membered cyclo-1,3,3,5,7,7-hexaphenyl-1,5-dibora-3,7-disiloxane and 4,4ˈ-bipyridine, 1D adduct - Bull, Okpara Sergeant; Don-Lawson, Chioma; Nweke-Maraizu, Ugo (European Journal of Chemistry, 2024)
Simple adducts of cyclo-diboradisiloxanes (Lewis acid) and amines (Lewis base) have been reported in the literature. However, the method for the synthesis of an 8-membered cyclo-diboratetrasiloxane, as well as its adducts, was modified in this report to save cost and achieve new results. In the literature, the synthesis of cyclo-1,3,3,5,7,7-hexaphenyl-1,5-dibora-3,7-disiloxane (Ph6B2Si2O4) (3) has been reported using diphenylsilanediol and phenylboronic acid and a Dean-Stark apparatus for the removal of water. However, in this study, molecular sieves were used for the facile removal of water, and the crude product recrystallized from diethyl ether and petroleum ether (3:1 ratio) to give compound 3. Compound 3 was reacted with 4,4’-bipyridine in a mixture of diethyl ether and petroleum ether solvents at reflux to give a 1D polymer [Ph6B2Si2O4]·L1 (4). Furthermore, compound 4 was characterized with various characterization methods such as single-crystal XRD, nuclear magnetic resonance, and FT-IR spectroscopy. The single crystal X-ray diffraction studies shows that the title compound crystalizes in the triclinic crystal system in the centrosymmetric space group P-1, a = 10.9372(4) Å, b = 18.4221(6) Å, c = 19.4697(6) Å, α = 70.533(3)°, β = 86.476(3)°, γ = 88.517(3)°, V = 3691.6(2) Å3, Z = 2, T = 173.0 K, μ(MoKα) = 0.122 mm-1, Dcalc = 1.204 g/cm3, 21463 reflections measured (5.196° ≤ 2Θ ≤ 56.45°), 14525 unique (Rint = 0.0185, Rsigma = 0.0483) which were used in all calculations, the final R1 was 0.0721 (I > 2σ(I)) and wR2 was 0.2143 (all data) with the 8-membered cyclo-1,3,3,5,7,7-hexaphenyl-1,5-dibora-3,7-disiloxane (Ph6B2Si2O4) (3) configuration.